Establishment and application of multiple cross displacement amplification coupled with lateral flow biosensor (MCDA-LFB) for visual and rapid detection of Candida glabrata - Yan Yuan; Yuhong Zhou; Yanfeng Zhou; Rui Ye; Jingrun Lu; Yizhe Wang; Fang Wei; Fukuan He; Honglan Yu; Yu Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Isolation, characterization, and genomic analysis of phage MY02 targeting extended-spectrum beta-lactamase-producing Klebsiella pneumoniae - Mengya Wang; Hailin Jiang; Chuhan Wang; Chunyan Zhao; Jinghua Li; Yanbo Sun; Xin Yu; Honglan Huang (Archives of Virology, 2025)

Biomimetic nanoparticles enhanced multiple myeloma treatment by removing chemokine (C-C motif) ligand 3 and synergizing PD-L1 blockade - Bo Zhang; Honglan Wang; Zhihao Xing; Huiwen Liu; Xinyue Deng; Xifeng Qin; Xiaomin Su; Jiayi Wu; Ruizhe Xu; Chunyan Sun; Yu Hu; Zhiqing Pang (Chemical Engineering Journal, 2025)

The impacts and outcomes of sustainable servitisation: A systematic literature review - Qijun Zhou; Honglan Yu; Kweku Adams; Rexford Attah-Boakye; Jeaneth Johansson (Journal of Cleaner Production, 2024)

Accurate and rapid quantification of PD-L1 positive exosomes by a triple-helix molecular probe - Zhichao Fan; Qin Weng; Yingxue Li; Tian Zeng; Junyi Wang; Honglan Zhang; Hua Yu; Yan Dong; Xiang Zhao; Jianjun Li (Analytica Chimica Acta, 2023)

Characterization and genomic analysis of JC01, a novel bacteriophage infecting Cronobacter sakazakii - Jie Jiang; Guanda Lan; Jinghua Li; Jun Yu; Honglan Huang; Yanbo Sun; Cuiting Xu; Dandan Liu; Yunwei Gong; Chunyan Zhao (Archives of Virology, 2023)
The lytic bacteriophage JC01 was isolated using a strain of Cronobacter sakazakii previously isolated from powdered infant formula (PIF). The complete genome sequence of phage JC01 was determined. The double-stranded DNA genome of phage JC01 is composed of 61,736 bp with a G + C content of 58.9%, and it contains 76 putative open reading frames (ORFs) without any tRNA genes. The predicted ORFs were classified into functional groups, including DNA manipulation, transcription, phage packaging, phage structure, host lysis, and hypothetical proteins. Based on overall nucleotide sequence comparisons, calculation of phage intergenomic similarities, and phylogenetic analysis, JC01 appears to be a novel bacteriophage infecting C. sakazakii .

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Dietary B vitamin and methionine intakes and lung cancer risk among female never smokers in China - Yumie Takata; Qiuyin Cai; Alicia Beeghly-Fadiel; Honglan Li; Martha J. Shrubsole; Bu-Tian Ji; Gong Yang; Wong-Ho Chow; Yu-Tang Gao; Wei Zheng; Xiao-Ou Shu (Cancer Causes & Control, 2012)

Measles incidence rate and a phylogenetic study of contemporary genotype H1 measles strains in China: is an improved measles vaccine needed? - Jingwei Shi; Jingtong Zheng; Honglan Huang; Yu Hu; Jiang Bian; Deqi Xu; Fan Li (Virus Genes, 2011)